Pengaruh personal branding, tingkat kepuasan, trust, dan motivasi berkoperasi terhadap loyalitas anggota Koperasi Simpan Pinjam Pembiayaan Syariah (KSPPS) “Bina Bersama” Lampung Utara - Miswanto , Miswanto; Sirait, Dian Rumintang Irianti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of personal branding, level of satisfaction, trust, and motivation of cooperatives on the loyalty of members of the Sharia Financing Savings and Loans Cooperative